Implementasi Seismik Refraksi Metode Hagiwara untuk Pendeteksian Bidang Gelincir di Sempadan Sungai Daerah Perumahan Sungai Bangek - Humaira Aryanti Khaidir; Ahmad Fauzi Pohan (Jurnal Fisika Unand, 2025)
The rapid development in the riparian zone of the Bangek River, Koto Tangah District, Padang City, has the potential to increase the risk of geological hazards such as landslides. This study aims to identify the subsurface structure and the presence of slip surfaces in the riverbank area that is being developed into a residential zone, using the Hagiwara method. Data acquisition was carried out along two survey lines, oriented perpendicular and parallel to the river, with offsets of 40 m and 30 m, respectively, employing four geophones and a 10 kg hammer as the seismic source. The interpretation results from the first survey line indicate that the subsurface consists of unsaturated sand and weathered layers, with evidence of a slip surface at a distance of 0–18 m and depths ranging from 0.7–4 m. This slip surface is located within a permeable layer with a low seismic velocity (368.955 m/s), overlain by an impermeable layer with a higher velocity (642.508 m/s). Meanwhile, the second survey line reveals a relatively homogeneous structure composed of weathered layers with varying densities. The Hagiwara interpretation identifies a slip surface along the second refractor, indicating potential slope instability within the first layer characterized by a low seismic velocity (449.165 m/s), suggesting weaker rock compaction. The information regarding the presence and depth of the slip surfaces identified in this study provides an important reference for development planning to mitigate the potential risk of landslides in the Bangek River riparian zone.